2015
DOI: 10.2147/ott.s80518
|View full text |Cite
|
Sign up to set email alerts
|

The significance of combining VEGFA, FLT1, and KDR expressions in colon cancer patient prognosis and predicting response to bevacizumab

Abstract: Targeting angiogenesis through inhibition of the vascular endothelial growth factor (VEGF) pathway has been successful in the treatment of late stage colorectal cancer. However, not all patients benefit from inhibition of VEGF. Ras status is a powerful biomarker for response to anti-epidermal growth factor receptor therapy; however, an appropriate biomarker for response to anti-VEGF therapy is yet to be identified. VEGF and its receptors, FLT1 and KDR, play a crucial role in colon cancer progression; individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Similarly, mixed results have also been observed in phase III trials in lung 34 , 35 and colon cancers 36 , 37 . Together with our previous findings in lung and colon cancer patient cohorts 28 , 29 , our results suggest that this three-gene signature may have clinical application in terms of predicting response towards anti-angiogenic agents in various types of cancer, and that this warrants further clinical evaluation, especially in a prospective trial setting.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similarly, mixed results have also been observed in phase III trials in lung 34 , 35 and colon cancers 36 , 37 . Together with our previous findings in lung and colon cancer patient cohorts 28 , 29 , our results suggest that this three-gene signature may have clinical application in terms of predicting response towards anti-angiogenic agents in various types of cancer, and that this warrants further clinical evaluation, especially in a prospective trial setting.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, in the present study, we have shown that co-expression of these genes also confers prognostic significance in glioma, suggesting that VEGFA - FLT1 - KDR three-gene signature may be a potential prognostic indicator for glioma patients. We previously reported that expression profiling of this three-gene signature could also predict response to bevacizumab in colon cancer patients 29 . Bevacizumab is an anti-angiogenic agent that has also been shown to be effective in glioblastoma patients; as no dataset comprising glioblastoma patients who have received bevacizumab exist in the public domain, and as there is also a lack of success in identification of biomarker for anti-angiogenic agents 30 , the value of this three-gene signature for prediction of response to bevacizumab in glioblastoma patients warrants further investigation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sox10 is a member of the SOX transcription factor family, which regulates canonical Wnt/β-catenin signaling; therefore, elevated Sox10 expression has been suggested to promote tumor progression [34]. Kdr(Vegfr2) plays a crucial role in colon cancer progression; thus, heightened Kdr expression can predict a poor prognosis in colon cancer patients [35]. Mcm2 regulates DNA replication; therefore, an enhanced Mcm complex including Mcm2 has been suggested to regulate various types of tumor development [36].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the expression of this three-gene signature ( VEGFA , VEGFR1 , and VEGFR2 ) was reported to represent robust prognostic indicator in this patient population. 40 …”
Section: Biomarkers Of Angiogenesismentioning
confidence: 99%